Numerical modeling and optimization study for the geometry of film cooling holes - Alshehaby, Mohammad Mahmoud (AUC Knowledge Fountain, 2019)
Film cooling is one of the essential approaches developed to protect the gas turbine blades and vanes from the passing, very high temperature, gases. It does so through covering the surface with a film of coolant air. Experimental and numerical studies have identified the important parameters affecting the film cooling aerodynamic and thermal behavior. Nevertheless, researchers are still concerned with more enhancement of film cooling performance through deeper understanding of the parameters that control coolant jet behavior. Being an important controlling parameter, the coolant nozzle geometry has been optimized in the current study. The analysis was performed in terms of adiabatic film effectiveness and heat transfer coefficient. The remaining key parameters were neutralized through fixing the coolant pipe inlet area and the pitch-to-hole-width ratio. Realizable k-Îµ model with scalable wall function has been selected to perform the current numerical study, being the most suitable RANS-based tested model in predicting the experimentally reported film cooling indicators at the blowing ratio of one. After proving the model accuracy, it was utilized to verify the cooling superiority of the racetrack slot (rectangular slot with fully round ends) over the typical round hole. Afterwards, the cooling performance of the racetrack slot was investigated at different aspect ratios. The optimum recorded racetrack geometry, having an aspect ratio of seven, served as a starting point for further optimization of the coolant pipe shape utilizing ANSYS Fluent Adjoint solver. The numerical optimization tool allows for a powerful, less-constrained, irregular shape optimization. Starting from the optimum racetrack geometry, the optimum irregular pipe shape was designated in two optimization steps, through which the average adiabatic film effectiveness over the test surface has increased from 0.24 to 0.34.